Insurgent - Roth, Veronica (Roth, Veronica. Divergent series., 2012)
"As war surges in the dystopian society around her, sixteen-year-old Divergent Tris Prior must continue trying to save those she loves--and herself--while grappling with haunting questions of grief and forgiveness, identity and loyalty, politics and love"--